Salah-al-Din - al-Ayyubi’s Actions to Eliminate Ismaili thought in Egypt and Protect its Intellectual Security - Mohammed Abbas, Jassem (International Journal of Psychosocial Rehabilitation, 2020)
This research has dealt with the protection of intellectual security in Egypt during the reign of Salah al-Din al-Ayyubi, which means the intellectual domination of the Ayyubid authority that conquered the freedom of Egyptian public opinion and confiscated its freedoms and ideas. The ideas carried by this doctrine aimed at reviving the new Sunni doctrine in Egypt to face Ismaili thought, using various means and procedures, including the marginalization of the Fatimid caliph and curtail his role to pave the way for the abolition of the Fatimid caliphate, as well as other strict measures; we will show that later.